Intravenous to Oral Stepdown Antibiotic Therapy: Another Cost-Effective Strategy in an Era of Shrinking Health Care Dollars - Thomas J Louie (Canadian Journal of Infectious Diseases)
The rapid transition from intravenous to oral antimicrobial therapy in hospitalized patients is being catalyzed by the need to gain further efficiencies in health care delivery without Compromising patient cure. The successful transition to oral therapy reduces complication from intravenous access devices. reduces cost of therapy and facilitates early discharge. both older and newer antimicrobials can be used as stepdown therapy. Although there are gaps in our information base with regards to outcome studies. the application of newer “pharmacodynamic” principles of antimicrobials action and careful selection of antimicrobials based on in vitro activity and pharmacokinetics will maximize the effectiveness of stepdown treatment of infections.